MNEs and the practice of international business diplomacy. Issue 1 (February 2022) - Doh, Jonathan P.; Dahan, Nicolas M.; Casario, Michelle
Highlights: We review International Business Diplomacy (IBD) scholarship. We develop a clearer conceptualization of IBD as a set of practices MNEs use to implement their global non-market strategy. We identify two global institutional governance aspects that impact IBD: governance level and institutional rule formality. We show how MNEs adapt IBD practices when policies are at differing governance levels and rules are more/less formal. We conclude by suggesting how our conceptualization and framework can be used to inform IB theory and practice. Abstract: Scholars of international relations and international political economy have long documented international business diplomacy (IBD) as a practice of multinational enterprises (MNEs), although the specific practices involved have not been consistently established in international business scholarship. We apply "practice theory" to position IBD within the realm of MNEs' global non-market strategy (NMS), arguing that IBD constitutes a set of practices in the implementation of global NMS, and that the most appropriate practices depend upon two key dimensions of the global institutional governance regime faced by the MNEs: the governance level and the degree of rule formality.